2022
DOI: 10.3389/fgeed.2022.785698
|View full text |Cite
|
Sign up to set email alerts
|

Promoterless Gene Targeting Approach Combined to CRISPR/Cas9 Efficiently Corrects Hemophilia B Phenotype in Neonatal Mice

Abstract: Many inborn errors of metabolism require life-long treatments and, in severe conditions involving the liver, organ transplantation remains the only curative treatment. Non-integrative AAV-mediated gene therapy has shown efficacy in adult patients. However, treatment in pediatric or juvenile settings, or in conditions associated with hepatocyte proliferation, may result in rapid loss of episomal viral DNA and thus therapeutic efficacy. Re-administration of the therapeutic vector later in time may not be possibl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 48 publications
(83 reference statements)
0
2
0
Order By: Relevance
“…Similarly, in recent work the Alb-targeted expression of FIX efficiently corrected Hemophilia B in neonatal mice, yet it was inadequate in adult mice. 25 To increase the efficiency of gene targeting at the Alb locus, Tsuji et al administered ribonucleotide reductase inhibitors to neonatal and juvenile mice resulting in enhanced targeted integration. 8 However, the effectiveness of this strategy still needs to be evaluated in the adult liver, where HDR is rare.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, in recent work the Alb-targeted expression of FIX efficiently corrected Hemophilia B in neonatal mice, yet it was inadequate in adult mice. 25 To increase the efficiency of gene targeting at the Alb locus, Tsuji et al administered ribonucleotide reductase inhibitors to neonatal and juvenile mice resulting in enhanced targeted integration. 8 However, the effectiveness of this strategy still needs to be evaluated in the adult liver, where HDR is rare.…”
Section: Discussionmentioning
confidence: 99%
“…HDR accurately corrects or removes a DNA lesion through synthesizing new DNA based on existing homology sequences [ 28 ]. Targeted gene insertion via the HDR mechanism requires donors carrying flanking homology arms of approximately 0.6–1.4 kb [ 29 35 ]. The long homologies facilitate the HDR repair of not only site-specific DSBs induced by a nuclease but also endogenous DNA lesions within a large region, which can lead to low frequency gene insertion in the absence of nuclease.…”
Section: Strategies For Targeted Dna Insertion For In Vivo Therapy Vi...mentioning
confidence: 99%
“…Furthermore, neonatal hepatocytes exhibit active proliferation; however, proliferation ceases in the adult stage. Lisjak et al [121] suggested caution when F9-KO newborn mice are subjected to tail vein injection of rAAV carrying human F9 cDNA to rescue the bleeding phenotype. The treated mice had detectable levels of F9 in the plasma and liver.…”
Section: Immunological Tolerancementioning
confidence: 99%
“…This is due to the nature of juvenile hepatocytes, which show active cellular proliferation; during active cell proliferation, the rAAV vectors introduced inside a cell are lost. Based on these experiments, Lisjak et al [121] decided to use the CRISPR/SaCas9 platform, which could potentially be applied to the treatment of young patients with hemophilia. In contrast to juvenile hepatocytes, CNS neurons and skeletal muscle cells are non-proliferative.…”
Section: Immunological Tolerancementioning
confidence: 99%